Looking for Someone to Blame: Delegation, Cognitive Dissonance, and the Disposition Effect - CHANG, TOM Y.; SOLOMON, DAVID H.; WESTERFIELD, MARK M. (Journal of Finance, 2016)
ABSTRACT We analyze brokerage data and an experiment to test a cognitive dissonance based theory of trading: investors avoid realizing losses because they dislike admitting that past purchases were mistakes, but delegation reverses this effect by allowing the investor to blame the manager instead. Using individual trading data, we show that the disposition effect—the propensity to realize past gains more than past losses—applies only to nondelegated assets like individual stocks; delegated assets, like mutual funds, exhibit a robust reverse‐disposition effect. In an experiment, we show that increasing investors' cognitive dissonance results in both a larger disposition effect in stocks and a larger reverse‐disposition effect in funds. Additionally, increasing the salience of delegation increases the reverse‐disposition effect in funds. Cognitive dissonance provides a unified explanation for apparently contradictory investor behavior across asset classes and has implications for personal investment decisions, mutual fund management, and intermediation.